Body weight and the medial longitudinal foot arch: high-arched foot, a hidden problem? - Woźniacka, R. (Springer-Verlag, 2013)
This study had two objectives. First, to determine the prevalence of hollow (high-arched) and flat foot among primary school children in Cracow (Poland). Second, to evaluate the relationship between the type of medial longitudinal arch (MLA; determined by the Clarke’s angle) and degree of fatness. The prevalence of underweight, overweight, and obesity was determined by means of IOTF cut-offs with respect to age and gender. A sample of 1,115 children (564 boys and 551 girls) aged between 3 and 13 years was analyzed. In all age groups, regardless of gender, high-arched foot was diagnosed in the majority of children. A distinct increase in the number of children with high-arched foot was observed between 7- and 8-year olds. Regardless of the gender, high-arched foot was more common among underweight children. In the group of obese children, the biggest differences were attributed to gender. High-arched foot was the most frequently observed among boys. In all gender and obesity level groups, the flat foot was more common among boys than among girls. Conclusions: High-arched foot is the most common foot defect among children 3–13 years old regardless of gender. Flat foot is least frequently observed in children 3–13 years old. A statistic correlation between MLA and adiposity is observed. Stronger correlation is observed among girls.